2017
DOI: 10.1371/journal.pone.0171492
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia reduces VEGF-165 expression, but not osteogenic differentiation of human adipose stem cells under hypoxia

Abstract: Cryotherapy is successfully used in the clinic to reduce pain and inflammation after musculoskeletal damage, and might prevent secondary tissue damage under the prevalent hypoxic conditions. Whether cryotherapy reduces mesenchymal stem cell (MSC) number and differentiation under hypoxic conditions, causing impaired callus formation is unknown. We aimed to determine whether hypothermia modulates proliferation, apoptosis, nitric oxide production, VEGF gene and protein expression, and osteogenic/chondrogenic diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…During fracture healing, hypoxia re-establishes oxygen supply by promoting angiogenesis via VEGF (Leegwater et al, 2017;Schipani, Maes, Carmeliet, & Semenza, 2009), which is a key component of bone repair (Farre-Guasch et al, 2018;Wang et al, 2011). Our implicating that IL4Rα/mTOR is the major signaling pathway contributing to the osteopenic phenotype in Fbn1 +/− mice (Chen et al, 2015).…”
Section: Hasc Proliferationmentioning
confidence: 77%
See 1 more Smart Citation
“…During fracture healing, hypoxia re-establishes oxygen supply by promoting angiogenesis via VEGF (Leegwater et al, 2017;Schipani, Maes, Carmeliet, & Semenza, 2009), which is a key component of bone repair (Farre-Guasch et al, 2018;Wang et al, 2011). Our implicating that IL4Rα/mTOR is the major signaling pathway contributing to the osteopenic phenotype in Fbn1 +/− mice (Chen et al, 2015).…”
Section: Hasc Proliferationmentioning
confidence: 77%
“…During fracture healing, hypoxia re‐establishes oxygen supply by promoting angiogenesis via VEGF (Leegwater et al, ; Schipani, Maes, Carmeliet, & Semenza, ), which is a key component of bone repair (Farre‐Guasch et al, ; Wang et al, ). Our findings also showed that hypoxia strongly enhanced VEGF expression in hASCs by ~4.0‐fold at Day 2 and 7 (Figures a,b–a,b).…”
Section: Discussionmentioning
confidence: 99%
“…Mild hypothermia alleviates hypoxic ischemic damage and increases tolerance to hypoxia via small ubiquitin-like modifier proteins of marrow-derived MSCs 34 , 35 . Although hypothermia reduces the gene expression of vascular endothelial growth factor, it does not affect the differentiation or apoptosis of MSCs exposed to hypoxia 36 . It can be seen that cryo-temperature pretreatment can enable MSCs to realize their potential under harsh conditions.…”
Section: Discussionmentioning
confidence: 95%
“…It might also have implications for bone healing, as osteoblast activity is severely impaired and osteoclast activity promoted in murine calvarial cells subjected to 34 °C [13]. We previously determined that hypothermia reduces vascular endothelial growth factor 165 ( VEGF-165 ) protein expression under hypoxia, but we did not find the osteogenic differentiation of human adipose stem cells to be impaired [19]. Since the CFCT treatments in our study were applied intermittently for 30 min, the temperature drop is short-lived.…”
Section: Discussionmentioning
confidence: 99%